Comparison of the adolescent pregnancy outcomes between refugees and Turkish citizens - Arslan, Oğuz; Giray, Burak; Tuğ, Niyazi (The Turkish Journal of Pediatrics, 2024)
Background. Adolescent pregnant women have significant risk factors in terms of preterm birth, low birth weight, gestational and neonatal complications, and neonatal and infant deaths. In many countries, living as a refugee differs from living as a local citizen regarding education level, access to health services, and lifestyle. We aimed to compare the obstetric, perinatal, and neonatal outcomes of Turkish and refugee adolescent pregnant women admitted to a tertiary maternity center. Methods. The study was planned as a retrospective cross-sectional. We included adolescent pregnant women who delivered between February 2018 and August 2023. Adolescent pregnant women were divided into two groups, the Turkish group and the Syrian refugee group, and compared with each other. Results. One thousand and fifty-one Turkish and 742 refugee adolescent pregnant women were included in the study. Adolescent pregnancy rates are higher in refugees than in the Turkish group (p < 0.001). We found that maternal age (p < 0.001), preeclampsia rates (p=0.029), gestational age at delivery (p < 0.001), and cesarean delivery rates (p=0.02) were lower in refugee adolescent pregnant women. Furthermore, we found that the anemia rates (p < 0.001) and low birth weight newborn rates (p = 0.011) were higher in refugee adolescent pregnant women. Conclusions. Enhancing the outcomes of adolescent pregnancies among refugees necessitates a heightened focus on education regarding sexual reproduction, increased prenatal follow-ups, and enhanced training in family planning.